How to advocate for and promote the experience capitalization approach ? A few lessons from Nepal - Rai, Renuka (Technical Centre for Agricultural and Rural Cooperation, 2019)
The High Value Agriculture Project (HVAP), implemented by the Ministry of Agriculture and Livestock Development of Nepal and funded by the International Fund for Agricultural Development (IFAD), has taken different steps to adopt the experience capitalization approach, and has shared the main lessons drawn with other IFAD-funded programmes. In order to extend and monitor the uptake of this approach, it has introduced a "chain-mentorship" approach, helping it reach more staff members.